Determinan Pemilihan Profesi Akuntan Publik di Kalangan Mahasiswa Akuntansi - Fitri; Anggraeni, Dewi; Rabiyah, Ulfa; Azzahra, Nabila; Nurwahidah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine the factors that encourage students' interest in choosing the public accounting profession. The aim of this study is to identify the elements that motivate students to choose to work in society, in terms of financial rewards, personality, level of job security, ease of information, and work environment towards interest in becoming a public accountant. We hope that this research will provide a broader understanding of the reasons why students choose the public accounting profession. This research uses quantitative descriptive methods using multiple regression analysis using primary data in the form of statements given directly to respondents. Respondents were students with a total of 115 participants. The results show that interest in a career as a public accountant is not influenced by awards, level of security and ease of information, but on the contrary, personality and work environment are factors that generate interest in a career as a public accountant.